2021
DOI: 10.3389/fpsyg.2021.668883
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Teacher's Mental State Talk on Young Children's Theory of Mind: A Quasi-Experiment Study

Abstract: This study investigated the relationship between teachers' mental state talk and young children's theory of mind with a quasi-experiment. In total, 56 young children were assigned to the experiment group (meanage = 41 months, SD = 2.47, 46% girls) and the control group (meanage = 40.68 months, SD = 2.23, 43% girls). The experiment group was engaged in a 12-week intervention program with mental state talk in storytelling, casual conversations, and role-playing games, whereas the control group received no interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These studies suggest that educators within English-speaking cultures exhibit a greater tendency to use MSL and this seems to be a nature of language use underpinned by cultural factors. However, a recent quasi-experimental study in China has shed light on the potential for enhancing educators' use of MSL through effective language training programs (Wu et al, 2021). The results revealed that educators of experimental group who received MSL training used MSL more frequently during reading, daily conversations, and role-playing activities, and the corresponding children showed signi cantly improved performance in TOM tasks.…”
Section: Cultural Difference In Mslmentioning
confidence: 99%
“…These studies suggest that educators within English-speaking cultures exhibit a greater tendency to use MSL and this seems to be a nature of language use underpinned by cultural factors. However, a recent quasi-experimental study in China has shed light on the potential for enhancing educators' use of MSL through effective language training programs (Wu et al, 2021). The results revealed that educators of experimental group who received MSL training used MSL more frequently during reading, daily conversations, and role-playing activities, and the corresponding children showed signi cantly improved performance in TOM tasks.…”
Section: Cultural Difference In Mslmentioning
confidence: 99%